Inferiority Feelings pada Remaja di Panti Asuhan: Bagaimana Peran Pengasuh dalam Memberikan Dukungan Sosial? - Syarifah Nazma Farah Ubaidillah Al Djufri; Khoiriyah Ulfah (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the role of caregivers in supporting adolescent development, particularly in reducing feelings of inferiority at Husnul Khotimah Orphanage in Bandar Lampung. The research employed a qualitative approach using interviews, observations, and documentation. The findings indicate that caregivers play a central role by providing emotional, motivational, instructional, and instrumental support. This support is manifested through open and empathetic communication, academic guidance, positive reinforcement, and encouragement of adolescents’ participation in social and educational activities. The caregivers’ role helps adolescents feel safe, valued, and accepted, which contributes to increased self-confidence, self-regard, and social and academic abilities. However, caregivers face several challenges, including limited time, insufficient number of caregivers, differences in adolescents’ characteristics, and limited institutional facilities.